Comparison of Predicted Significant Coronary Lesion by Duke Treadmill Score among Coronary Heart Disease Risk Factors in Patients with Positive Ischemic Response Treadmill Test - David Rubiyaktho; Cholid Tri Tjahjono (ACI (Acta Cardiologia Indonesiana), 2018)
Background: According to Framingham Study, independent risk factors for coronary heart disease (CHD) are diabetes, hypertension, smoking, dyslipidemia, family history of CHD and obesity. Previous study reported cut-off value of Duke Treadmill Score (DTS) < -0.5 represents a significant coronary lesion with positive predictive value 88.4%. Objective: To compare the incidence of predicted significant coronary lesions by DTS among various risk factors for coronary heart disease. Methods: A cross sectional study was done on 292 patients age 18 to 74 years old who had positive exercise testing for CAD screening during period of June 1st 2016 until May 30th 2017. DTS was calculated from treadmill test as: exercise time - (5 x ST deviation in mm) - (4 x exercise angina). A coronary lesion was predicted significant with DTS cut off value < -0.5. Results: Subjects mean age was 57 years old, male were 60.4%. The risk factors for CHD were found sequentially from the most frequent were hypertension 51.9%, smoking 35.3%, diabetes mellitus 23.1%, dyslipidemia 11.9%, obesity 4.2% and family history of CHD 6.3%. It was found that diabetes was significantly different from its effect on DTS value with p value = 0.021, while hypertension, obesity, dyslipidemia and family history CHD had no significant effect. Logistic regression found consistently that diabetes was significant (p=0.019). Conclusion: Predicted significant coronary lesions by DTS developed more frequent in diabetes compared to, hypertension, smoking, dyslipidemia, obesity and family history of coronary heart disease.